2010
DOI: 10.2478/s11535-010-0085-2
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose ionizing radiation effects on differentiation of HL-60 cells

Abstract: The biological effects of low-dose radiation have attracted attention, but data are currently insufficient to fully understand the beneficial role of the phenomenon. In the present study, we have investigated the effects of low doses of gamma-irradiation alone and in combination with all-trans-retinoic acid (RA) on proliferation, apoptosis and differentiation of the human promyelocytic leukemia HL-60 cells. Changes in cell behavior and protein expression were determined with the use of light and fluorescent mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Regarding low-dose irradiation, some studies addressed the preventive effect of low-dose irradiation on CSC induction. Savickiene et al demonstrated that low-dose of gammairradiation (1-100 cGy) caused 25% of HL-60 cells undergoing differentiation, while only 3-5% of these cells underwent spontaneous differentiation (45) . Additionally, Kaushik et al observed that low-dose radiation suppressed EMT and CSC induction in breast cancer cells by inhibiting the Jak1/STAT3 signaling pathway (46) , which are inconsistent with the results of the present study in which all three genes are overexpressed at 0.1 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding low-dose irradiation, some studies addressed the preventive effect of low-dose irradiation on CSC induction. Savickiene et al demonstrated that low-dose of gammairradiation (1-100 cGy) caused 25% of HL-60 cells undergoing differentiation, while only 3-5% of these cells underwent spontaneous differentiation (45) . Additionally, Kaushik et al observed that low-dose radiation suppressed EMT and CSC induction in breast cancer cells by inhibiting the Jak1/STAT3 signaling pathway (46) , which are inconsistent with the results of the present study in which all three genes are overexpressed at 0.1 Gy.…”
Section: Discussionmentioning
confidence: 99%